Peran Madrasah Diniyah An Nur dalam Pengembangan Pendidikan Islam Melalui Tradisi Keagamaan - Irawan, Kukuh Adi; Ahyani, Hisam; Jafari, Ahmad; Rofik, Achmad (Prodi PAI STAI Sumatera Medan, 2021)
Madrasah Diniyah requires a special strategy in managing their educational institutions, as was done by Madrasah Diniyah An Nur Karangkobar Banjarnegara through religious traditions. However, there are still obstacles in its application, so this study aims to determine the role and contribution of Madrasah Diniyah An Nur in developing Islamic education through religious activities and to find out what obstacles are faced in developing it. The type of research used is field resesarch with a qualitative approach. Primary data were obtained from the Head of Madrasah, Ustadz and Ustadzah, Wali Santri, Santri Madrasa Diniyah An Nur Karangkobar. The results showed that the role of Madrasah Diniyah An Nur Karangkobar in developing Islamic education was carried out through religious activities such as; khithabah, barzanzi, qiroah, and muhadharah. Its role in the development of Islamic education is as: (1) an institution that teaches religious knowledge; 2) media for the preservation of Islamic teachings; 3) Media for moral cultivation; 4) pillars of Islamic education; The obstacles faced are: (1) there are students who are not fluent in reading the Qur'an and Arabic pegon, (2) lack of motivation both in terms of students, teachers and parents, (3) students are less active in scientific activities. The solutions are (1) improvement of better learning methods, (2) optimization of the performance of educators, (3) enforcement of sanctions